Clinicopathological study of salivary gland neoplasm (Bangladesh Journal of Otorhinolaryngology, 2010)
An observational study was done in 60 cases of benign and malignant salivary gland. Patients were collected from ENT Department of Dhaka Medical College Hospital, Dhaka during the period of September 2003 to August 2004. Here patients belonged to different age group range from 21 to 80 years. Parotid gland was involved in 50 cases and submandibular gland in 10 cases. In case of parotid gland 35 cases found benign and 15 cases were malignant. In submandibular gland benign and malignant cases were equal. Histopathological study showed, 60% were pleomorphic adenoma and 10% were Warthin's tumour in case of parotid gland. In malignant cases mucoepidermoid cases, adenoid cystic carcinoma were equal 10%. Common presenting feature was swelling, that is 100% followed by pain 26.66% and skin involvement in 8.3%. Duration of symptoms varies from 2 month to 12 years. In parotid tumours, superficial lobe was affected in 97.14%. All of the patients were treated surgically. In case of benign parotid tumour. Superficial parotidectomy was done in 97.14%. Total conservative parotidectomy was done in 2.85%. In case of malignant tumour, total conservative parotidectomy was done in 33.34% case, radical energy needed in 46.66%. Key words: Salivary gland neoplasmDOI: 10.3329/bjo.v15i1.4306 Bangladesh J of Otorhinolaryngology 2009; 15(1): 17-25